FEATURES OF CYTOKINE PRODUCTION IN PATIENTS WITH UNSTABLE ANGINA: DEPENDENCE ON ETHNICITY IN THE REPUBLIC OF SAKHA (YAKUTIA) - A. S. Golderova; I. N. Nikolaeva; V. E. Tarasova; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. We investigated levels of spontaneous and mitogen-induced cytokine production (IL-1β, IL-4, IL-6, IL-10 and IFNγ) by peripheral blood cells of 24 men with unstable angina (UA), including indigenous population (n = 12, Yakuts), and a group of Russian migrants to the Republic of Sakha (n = 12). Activation of inflammatory response was revealed in the total group of patients with UA, manifesting by increase of spontaneous and induced production of the pro-inflammatory IL-1β, IL-6 cytokines, and mitogen-induced production of IFNγ. As compared with healthy individuals, spontaneous and induced production of anti-inflammatory IL-4 was decreased in UA patients, whereas the mitogen-induced production of IL-10 proved to be enhanced. Therefore, it is highly possible that a pro-atherogenic Th1-immune response is developing during UA, along with suppression of Th2-driving response. The differences revealed for different ethnic groups suggest that severity and prevalence of atherosclerotic disease, which is more common in the non-native patients, is associated with increased production of pro-inflammatory IL-1β and IL-6 cytokines.